KAMUS VISUAL PEMBELAJARAN BIOLOGI SMA BERBASIS RISET DISTRIBUSI VEGETASI DASAR DI LAHAN GAMBUT PASCA KEBAKAARAN - Ridho Abdul Gani; Nursal Nursal; Yuslim Fauziah; L.N. Firdaus L.N. Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Interesting teaching materials in the learning process are usually printed and illustrated in one of the visual dictionaries. Visual Dictionary is one of the illustrated and constant teaching materials that facilitates learners to understand learning. This study aims to produce a visual dictionary of Biology High School learning using the results of a study on ecosystems in post-fire peatlands. For that reason, a survey was conducted in Rimbo Panjang Village, Kampar District, Riau Province in February - October 2017. Quadratic methods and purposive sampling techniques were applied to gradient fire events 2009, 2013, 2014, 2015, 2016 and 2017. The paramaeter were observed i.e. type composition, environmental factors and distribution pattern of vegetation. The data were analyzed using Dispers Morista Index descriptively and qualitatively. Based on the results of the research, 32 species and 21 basic vegetation families were found in post-fire peatlands. Distribution pattern of peatland vegetation shows that distribution patterns tend to be more random than clustering patterns. The result of this research can be used for the development of visual dictionary of Class X Biology (KD 3.10). Testing using visual dictionaries generated and the benefits of enriching the learners' learning materials are classically important for further action. Keywords : biology visual dictionary, post-fire peatland, species ditribution pattern, senior high school